INSTRUMEN PENILAIAN AUTENTIK PADA PEMBELAJARAN IPA KELAS VII SMP DI PEKANBARU - Darmawati "; Yustini Yusuf; Firda Wentymeses (Biogenesis, 2016)
ABSTRACTThe aim of study was to know the instruments are made of authentic assessment VII grade teacher for science learning material energy in living systems at the junior Babussalam Pekanbaru. Research conducted at the University Campus Biology Education FKIP Riau in August-September 2015. The subject of this study is made of authentic assessment instruments seventh grade teacher for science learning smaterial energy in living systems. How to analyze authentic assessment instruments which have been created by a teacher is to use assessment indicators. Indicator assessment made in accordance with the demands of the curriculum in 2013 for each competency. Competence of knowledge (cognitive) using indicators to assess the test instrument is written in narrative form, the competence of the attitude (affective), using indicators to assess the observations while competency skills (psychomotor) using indicators to assess the performance of the instrument. Results of the analysis instrument authentic assessment made classroom teachers VII for science learning material energy in living systems at the junior Babussalam Pekanbaru to note that the competence of knowledge (cognitive) for the written test in narrative form classified in sufficient criteria to the percentage of 61%, competence, attitudes (affective) assessment classified themselves in less criteria with 59% and the percentage of observations fall into the criteria very well with the percentage of 83% while the competency skills (psychomotor) for assessing performance in both criteria once classified with a percentage of 83%. Key words:Authentic assessment, IPA, junior high school